Silk fibroin–collagen hydrogel loaded with IGF1-CESCs attenuates intervertebral disk degeneration by accelerating annulus fibrosus healing in rats - Tian, Zhiqiang; Shen, Zigang; Chen, Hong; Zhao, Ping (Frontiers in Pharmacology, 2025)
Introduction: The self-healing capacity of a damaged annulus fibrosus (AF) leads to intervertebral disk (IVD) degeneration. AF wound treatment is challenging. The combination of biomaterials and stem cell-derived exosomes is a promising wound treatment strategy with significant clinical value.Methods: We isolate primary nucleus pulposus cells (NPCs) and primary annulus fibrosus cells (AFCs) from rats as the target cells of rat insulin-like growth factor 1(IGF1), and verify the proliferation and migration; constructed cartilage endplate stem cells (CESCs) engineered cells that release exosomes containing high concentrations of IGF1by lentiviral infection, and used the IGF1-CESCs combined with combined silk fibroin (SF) and a collagen-mixed hydrogel for the treatment of AF wounds in rat. Results: We found that both IGF1 and IGF1-rich exosomes (IGF1 Exo) promoted the proliferation and migration of AFCs. SF and collagen mixed hydrogels have excellent compressive mechanical properties and are suitable for use in IVD therapy. After the IGF1-CESCs@SF-collagen hydrogel was filled in the damaged area of the AF in rat, the wound healing was accelerated, nucleus pulposus overflow was inhibited, the IVD height was maintained, and degeneration was reduced. Discussion: The IGF1-CESCs@SF-collagen hydrogel can efficiently treat AF wounds and inhibit degeneration of IVD, and has potential for clinical treatment.